Diseño de un banco experimental para determinación de la velocidad de flotación de partículas sólidas con fines de transporte neumático. - Álvarez Murillo, Stalin Paúl (2021)
The present project deals with the design of a bench to determine the flotation velocity of particles, depending on the aerodynamic characteristics, which are transported through piping systems driven by an air blowing system, usually performed empirically because the characteristics of the particles are not known for sure, as well as the properties they have at the time of being transported through these pipes. To solve the problem regarding the characteristics and properties of the particles, the design of an experimental bench of flotation velocity through a pipe of constant diameter is proposed, in such a way that it is easier to determine the necessary characteristics of the objects of study in order to be able to carry out future transport systems that comply with specific design and construction standards. For the implementation of the test bench there is a universal blower, to which a piping system will be implemented, with a hopper for the feeding of the particles and with an open piping system for the elevation of the same in order to achieve a measurement according to the wind flow, in this way the companies that wish to implement this type of system will help them to reduce transport times, the objective is to determine the air flow velocities required for the flotation of solid particles, in order to use the results obtained for an adequate design of pneumatic conveying systems, as a consequence of this it was obtained that the pneumatic conveying velocity will have to be higher depending on the dimensions, as is the case of flour that needs a much lower air flow which is 5 m/s as opposed to white corn that moves at a velocity of 15.73 m/s.